'Addictive' for children and 'helpful' to parents: electronic devices as a non-human actor in family relations. Issue 3 (3rd July 2022) - Sikorska, Małgorzata
ABSTRACT: The main aim of the article is to analyze the role of electronic devices used by children in parents – children relationships. Starting with the assumption that material objects are non-human actors ('actants'), the author explores the parents' perspective on electronic devices, seen simultaneously as addictive for children and helpful to parents, and their impact on family practices. The thesis proposed is that electronic devices seem to actively influence and re-shape the power dynamics of families. Specifically, first the use of the devices by children reveals processes where children's influence appears to increase and parents' influence appears to decrease. Secondly, the way in which parents attribute agency to electronic devices reveals their anxieties and uncertainties about raising children, and about parenthood in general. The article is based on the results of qualitative research: in - depth interviews with 54 parents (including: 24 parental couples and 6 single parents). Two rounds of interviews were conducted. The research was carried out in Poland: in Warsaw (the capital) and in a medium-sized town.